Exponential Convergence of Finite-Dimensional Approximations to Linear Bond-Based Peridynamic Boundary Value Problems (Communications in Mathematical Research, 2019)
In this paper, we demonstrate that the finite-dimensional approximationsto the solutions of a linear bond-based peridynamic boundary value problemconverge to the exact solution exponentially with the analyticity assumption of theforcing term, therefore greatly improve the convergence rate derived in literature.